Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.7759/cureus.35237
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of ChatGPT in Assisting to Solve Higher Order Problems in Pathology

Abstract: BackgroundArtificial intelligence (AI) is evolving for healthcare services. Higher cognitive thinking in AI refers to the ability of the system to perform advanced cognitive processes, such as problem-solving, decision-making, reasoning, and perception. This type of thinking goes beyond simple data processing and involves the ability to understand and manipulate abstract concepts, interpret, and use information in a contextually relevant way, and generate new insights based on past experiences and accumulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 19 publications
(19 reference statements)
2
53
0
2
Order By: Relevance
“…Based on our findings, ChatGPT is capable of providing answers to both first- and second-order knowledge questions with approximately 80% accuracy. This corroborates the findings of Sinha et al [ 4 ]. There was no difference in the application's capability to solve both types of questions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on our findings, ChatGPT is capable of providing answers to both first- and second-order knowledge questions with approximately 80% accuracy. This corroborates the findings of Sinha et al [ 4 ]. There was no difference in the application's capability to solve both types of questions.…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, natural language processing (NLP) and machine learning (ML) techniques have revolutionized the field of question-answering systems [ 1 ]. ChatGPT is one such artificial intelligence (AI) language model that has been trained to understand the nuances of natural language and provide accurate answers to a wide range of questions [ 2 , 3 , 4 ]. While ChatGPT has shown promising results in solving problems in various fields, its ability to accurately answer first- and second-order knowledge questions in microbiology has not been extensively evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous past investigations have evaluated the potential of ChatGPT for medical education purposes. The observation is similar to a recent study conducted by Sinha et al demonstrating the utility of ChatGPT for solving higher-order problems in pathology [12]. The study conducted by Das et al had a similar outcome where ChatGPT was shown to answer first and second-order questions of microbiology with 80% accuracy, thereby corroborating with our study [13].…”
Section: Discussionsupporting
confidence: 92%
“…ChatGPT was developed using data from The Common Crawl database, which includes copyrighted content from publishers, as well as works by individual authors and scholars [42]. There is a chance that the advice offered if ChatGPT is utilized to provide legal or financial advice could not be correct or current.…”
Section: Other Possible Lawful Effectsmentioning
confidence: 99%